2002
DOI: 10.1128/jb.184.7.1851-1858.2002
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an ADP-Ribosyltransferase Toxin (AexT) from Aeromonas salmonicida subsp. salmonicida

Abstract: An ADP-ribosylating toxin named Aeromonas salmonicida exoenzyme T (AexT) in A. salmonicida subsp. salmonicida, the etiological agent of furunculosis in fish, was characterized. Gene aexT, encoding toxin AexT, was cloned and characterized by sequence analysis. AexT shows significant sequence similarity to the ExoS and ExoT exotoxins of Pseudomonas aeruginosa and to the YopE cytotoxin of different Yersinia species. The aexT gene was detected in all of the 12 A. salmonicida subsp. salmonicida strains tested but w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
74
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 33 publications
0
74
0
1
Order By: Relevance
“…salmonicida [38]. This system is responsible for the translocation of the ADPribosylating toxin, AexT, into the cytosol of target fish cells and is associated with the pathogenicity of the bacterium [37,39,40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…salmonicida [38]. This system is responsible for the translocation of the ADPribosylating toxin, AexT, into the cytosol of target fish cells and is associated with the pathogenicity of the bacterium [37,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…A type III secretion system (TTSS) has also been identified in A. salmonicida subsp. salmonicida Strain JF2267, a strain originally isolated from Arctic char Salvelinus alpinus presenting typical furunculosis symptoms [37,38]. Studies relating to Aeromonas virulence have identified a type III secretion system in A. salmonicida subsp.…”
Section: Discussionmentioning
confidence: 99%
“…This is believed to be the first study that has investigated the in vivo behaviour of A. salmonicida TTSS effectors by conducting animal challenges with mutants deleted in three effector genes. A. salmonicida TTSS effectors are poorly characterized compared with those of other systems; only the functionality of AexT has been studied in any detail (Braun et al, 2002(Braun et al, , 2003b(Braun et al, , 2005. The in vivo behaviour of the three effector mutant strains mimicked the behaviour of a suite of effector mutant strains created in Y. enterocolitica O : 8 (Trülzsch et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Three TTSS effectors were also identified. One, AexT, was chromosomally located, had 100 % amino acid identity to a previously characterized translocated ADP-ribosylating cytotoxin from A. salmonicida strain JF2267 and had similarity to exoT of P. aeruginosa (Braun et al, 2002(Braun et al, , 2003b. The other two, located on plasmid pAsa5, were termed aop (Aeromonas outer protein) H and aopO, with similarity to Yersinia yopH and yopO/ypkA, respectively (Table 3).…”
Section: Identification Of Ttss Genesmentioning
confidence: 99%
“…This study focuses on the recently identified ADP ribosyltransferase toxin A.salmonicida exoenzyme T, or AexT, which has recently been shown to play a role in the cytotoxicity of A. salmonicida subsp. salmonicida to fish cells (4).…”
mentioning
confidence: 99%